2021
DOI: 10.3389/fcell.2020.571948
|View full text |Cite
|
Sign up to set email alerts
|

The Adipose Microenvironment Dysregulates the Mammary Myoepithelial Cells and Could Participate to the Progression of Breast Cancer

Abstract: Breast cancer is the most common cancer among women worldwide. Overweight and obesity are now recognized as established risk factors for this pathology in postmenopausal women. These conditions are also believed to be responsible for higher recurrence and mortality rates. Reciprocal interactions have been described between adipose and cancer cells. An adipose microenvironment favors a greater proliferation of cancer cells, their invasion and even resistance to anti-cancer treatments. In addition, the chronic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Leading theories point to chronic in ammation and the release of in ammatory cytokines from ASCs as a potential driver for breast cancer progression [12,13]. Most previous studies have only characterized the biology of ASCs from the abdomen [7,14].…”
Section: Discussionmentioning
confidence: 99%
“…Leading theories point to chronic in ammation and the release of in ammatory cytokines from ASCs as a potential driver for breast cancer progression [12,13]. Most previous studies have only characterized the biology of ASCs from the abdomen [7,14].…”
Section: Discussionmentioning
confidence: 99%
“…IHC results indicated that CMT-1026 was a basal epithelial cell line, and its positive expression of cytokeratin 5/6 (for basal epithelial cells) (55), α-SMA (for myoepithelial cells) (56), and P63 (for myoepithelial cells) (57) indicated that CMT-1026 was of epithelial origin. CMT cells frequently show myoepithelial proliferation leading to preinvasive carcinoma (58,59). CMT-1026 is also a well-established basal like subtype cell line (60).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental results showed that adipose cells led to a decrease in the viability of myoepithelial cells (MECs), which are known as tumor suppressor cells that block the transition from ductal carcinoma in situ to invasive carcinoma. Both leptin amplification and the disruption of genes involved in extracellular matrix maintenance were observed during this stage [51]. The effect of the adipokine leptin on normal mammary epithelial cells was investigated.…”
Section: Leptin and Breast Cancermentioning
confidence: 99%